2005
DOI: 10.1158/0008-5472.can-04-4608
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Polyploidy by Histone Deacetylase Inhibitor: A Pathway for Antitumor Effects

Abstract: Histone deacetylase (HDAC) inhibitors can induce various transformed cells to undergo growth arrest and/or death. Suberoylanilide hydroxamic acid (SAHA) is an HDAC inhibitor which is in phase I/II clinical trials and has shown antitumor activity in hematologic and solid tumors at doses well tolerated by patients. HDAC is the target for SAHA, but the mechanisms of the consequent induced death of transformed cells are not completely understood. In this study, we report that SAHA induced polyploidy in human colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 46 publications
6
71
0
1
Order By: Relevance
“…G 1 and G 2 arrests are largely associated with induction of p21, which inhibits CDKs regulating G 1 progression (CDK4/6) and G 1 /S transition (CDK2), the activity of proliferating cell nuclear antigen that is required for DNA replication (Vidal and Koff, 2000), and cdc2/CDK1 that regulates G 2 /M transition. Loss of p21 abolishes HDACi-induced G 1 arrest (Archer et al, 1998;Rosato et al, 2001;Xu et al, 2005). G 1 arrest was observed in cells without p21 (Hitomi et al, 2003).…”
Section: Hdaci Induces Cell Cycle Arrestmentioning
confidence: 99%
See 2 more Smart Citations
“…G 1 and G 2 arrests are largely associated with induction of p21, which inhibits CDKs regulating G 1 progression (CDK4/6) and G 1 /S transition (CDK2), the activity of proliferating cell nuclear antigen that is required for DNA replication (Vidal and Koff, 2000), and cdc2/CDK1 that regulates G 2 /M transition. Loss of p21 abolishes HDACi-induced G 1 arrest (Archer et al, 1998;Rosato et al, 2001;Xu et al, 2005). G 1 arrest was observed in cells without p21 (Hitomi et al, 2003).…”
Section: Hdaci Induces Cell Cycle Arrestmentioning
confidence: 99%
“…Normal cells are relatively resistant to HDACi-induced cell death (Burgess et al, 2004;Insinga et al, 2005;Ungerstedt et al, 2005). The cell death pathways identified in mediating HDACiinduced transformed cell death include apoptosis (Rosato and Grant, 2005;Bolden et al, 2006;Minucci and Pelicci, 2006) by the intrinsic (Ruefli et al, 2001) and extrinsic pathways, mitotic catastrophe/cell death (Qiu et al, 2000;Dowling et al, 2005;Xu et al, 2005), autophagic cell death (Shao et al, 2004), senescence and reactive oxygen species (ROS)-facilitated cell death (Rosato and Grant, 2005;Ungerstedt et al, 2005). The response to HDACi appears to depend, in part at least, on the nature of HDACi, concentration and time of exposure, and importantly, the cell context.…”
Section: Hdaci-induced Antitumor Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, hydroxamic-based HDACIs, such as ABHA, SAHA and SK-7068, induced tumor-selective mitotic defects while normal cells remained unaffected. 14,103,104,110 Lastly, several chimeric oncoproteins characteristic of cancer cells are selectively targeted by HDACIs. HDACIs specifically inhibit PML-RARα in PML cells, resulting in re-expression of RARα responsive genes.…”
Section: Molecular Basis Of Hdacis In Cancer Therapymentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In addition, HDACIs have the advantage of being less toxic in normal cells than in cancer cells. [10][11][12][13][14] Based on their pleiotropic cellular effects and their tumor-selectivity, several HDACIs are currently undergoing clinical trials, and some of them have shown promising anti-tumor activity. [15][16][17][18][19][20][21] While it is clear that HDACIs directly modulate gene transcription by histone hyperacetylation, the molecular underpinnings of their cytotoxicity and tumor-selectivity remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%